Water resources development by the U.S. Army Corps of Engineers in Virginia. - United States. Army. Corps of Engineers. North Atlantic Division. ([Norfolk, Va.] : U.S. Army Engineer District, Norfolk, Corps of Engineers, North Atlantic Division, 1957)
Vols. for <1965-1971> published: New York, N.Y. : U.S. Army Engineer Division, North Atlantic. Title from cover. Mode of access: Internet. Issued by the U.S. Army Corps of Engineers, North Atlantic Division. Continued by: Water resources development in Virginia. 2